Antimicrobial and antioxidant potentials of callus cultures of Convolvulus microphyllus Sieb. ex Spreng. - Boskey Pancholi; M Gautam (Islamic Azad University, Shahrekord Branch, 2022)
Background & Aim: Convolvulus microphyllus Sieb. ex Spreng. (Family: Convolvulaceae) known as "Shankhpushpi" is reported to be brain tonic and useful in CNS disorder, hypertension, thyrotoxicosis and ulcer. Tissue culture technique has been optimized for the large scale production of medicinally important plant independent from climatic and geographic conditions. Antioxidant and antimicrobial activities were performed and compared with in vivo. Active compounds with biological activities were isolated, identified from the callus extracts. These biological constituents can be propagated in large amount with low cost use tissue culture techniques. Experimental: Cell cultures of C. microphyllus have been established using Murashige and Skoog's (MS) medium supplemented with different concentrations of 2,4-dichlorophenoxyacetic acid (2, 4-D). Callus was harvested at different time intervals of 2, 4, 6 and 8 weeks and their antimicrobial and antioxidant potentials along with the isolation of active compounds isolation were carried out using established protocols. Results: Ethanolic extracts of 2 weeks-old callus demonstrated appreciable antifungal activity against Penicillium chrysogenum and Tricophyton rubrum (inhibition zone of 14.66 ± 0.66 and 14.00 ± 0.57 mm respectively) while maximum antibacterial activity was recorded in 6 and 4 weeks-old callus against Klebsiella pneumoniae (Inhibition zone of 14.66 ± 0.61 mm and 14.33 ± 0.59 mm respectively). Antioxidant potentials were more in plant extract (IC50 0.055 mg/ml and 510 ± 20.02 ascorbic acid equivalents) as compared to callus. Phenolic acids viz., caffeic-, p- coumaric-, ferulic-, gallic-, vanillic- and syringic acids were isolated and screened for antimicrobial efficacy. Recommended applications/industries: The callus extract shows similar results as that of In vivo plant. Two week old callus exhibit most profound antifungal and 4 to 6 week for antimicrobial activities. Callus extract shows similar bio-potentials and secondary metabolites level, so it can be used for large scale production of biologically active phytochemicals with antimicrobial properties.